Kegiatan Pembuatan Eco Enzyme untuk Pengelolaan dan Pengolahan Limbah Cair-A pada Instalasi Pengolahan Air Limbah di RSUD Tabanan - Ida Ayu Putri Genta Widyasari; Tude Guntur Bayu Wisnu; Ni Putu Maharani Wulandari P. (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2023)
In this service, RSUD Tabanan experienced problems with organic waste that accumulated in the trash can and the liquid waste channel had an unpleasant smell. This service uses a qualitative descriptive method with the technique of literature review method, field survey method, interview method, data analysis method. This service aims to solve the problems being faced by Tabanan Hospital related to organic waste and channels that smell pungent. The solution provided by the service team is to make eco enzyme and pour it into the liquid waste channel gradually so that the bacteria that produce unpleasant odours can be decomposed.